Unlocking the Multi-Faceted Reactivity of 4-Hydroxythiocoumarin: Sustainable Synthesis of Novel Hybrid Heterocyclic Scaffolds with Therapeutic Potential - Goswami, Ujjwal Jyoti (My University, 2025)
The contents of this thesis are organized into five chapters encompassing a systematic exploration of the synthetic versatility and reactivity of 4-hydroxythiocoumarin, aimed at developing sustainable methodologies for the construction of novel sulfur-containing heterocyclic hybrids with potential therapeutic relevance.
Khan, Abu Taleb